Sustainability and Halal: Procedure, Profit and Ethical Practice - Tayob, Shaheed (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Halal certification is a technological and technocratic transformation that facilitates increasingly complex food production and global supply chain management. However, the discourse and materiality of global trade and the growth of consumers for which halal certification is in demand have been the target of ethical criticism that puts forward the vulnerabilities of human, non-human, and environmental relations. This paper proceeds through some steps to elucidate questions of halal ethics in practice, halal certification, and Muslim trade and exchange networks. The research method uses a descriptive qualitative approach, using library sources. The results of the analysis and discussion show that the halal discursive tradition that centralizes intra-Muslim networking, trade, and exchange, is significant to consider the ethical stakes of halal certification for marginalized and precarious Muslim populations around the world. Drawing on ethnographic insights on the meat market in Mumbai, I argue that exclusive political intimacy and economic growth mean halal certification can play a part in the marginalization of the Muslim workforce and trade in the city. Therefore, the question of sustainability and halalness must consider the new formation of halal's ethical requirements to bridge the gap between the ethics of trade and intra-Muslim exchange and global trade conditions.